Graph-Theoretic Analysis for Sustainable Urban Structure : A Case Study of Lower Manhattan's CBD - mutaz, tamara; khalid, zainab (Enquiry The ARCC Journal for Architectural Research, 2025)
A significant challenge arises in the characterization of urban systems, especially regarding the intricate structures of Central Business Districts (CBDs). Conventional models seem insufficient, failing to comprehend the non-linear, network-oriented structure of the city's economic and social dynamics. This creates a disparity between the city's physical, geographical structure and the unseen processes occurring within it. The fundamental inquiry is thus configurational: how can we systematically examine the inherent spatial logic of the CBD to develop a more efficient and predictive planning model? This paper presents a theoretical and methodological model to explore this inquiry, which focuses on Lower Manhattan as the primary subject of analysis. The aim of the research is to develop an analytical model that fosters a relational comprehension of the city as a system. The methodology combines graph-theoretic mathematical coding with spatial syntax analysis to elucidate the fundamental structure of dynamics in the Central Business District. We evaluate vulnerability as an intrinsic characteristic of network topology, apply Prüfer’s code to determine its distinctive structural signature, and employ various syntactic methods to examine its spatial configuration. Q-analysis, Zipf's law, Markov chains, and fractal analysis elucidate the interconnectedness of shape, function, and temporal change in various dimensions. The findings indicate that the layout of Lower Manhattan possesses a complex, robust, and well-structured network topology. We observed correlations between spatial integration indices and economic activity patterns; that is, the grid is an essential component of the economic functionality. The proposed model is both predictive and quantitative, which activates the comprehension of urban complexity. The systematic relationship elucidates the connection among geographical form, economic function, and susceptibility to potential threats. This framework offers a model for urban planners and designers to enhance connectivity, pinpoint structural deficiencies, and devise solutions that promote sustainable, resilient, and economically viable urbanism.